A porous polymer humidity sensing material with fast response and recovery characteristics and a preparation method thereof

The porous polymer film is prepared by using a mixed dispersion of conductive filler and water-soluble polymer in the humidity sensor, and forming a porous structure through non-solvent exchange, which solves the problem of long response and recovery time of the existing humidity sensor, and achieves the effect of rapid response and recovery.

CN115219565BActive Publication Date: 2025-03-14ZHEJIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210674129.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-14
Publication Date
2025-03-14
Estimated Expiration
2042-06-14

AI Technical Summary

Technical Problem

The existing polymer-based humidity sensors have problems with long response and recovery times, and it is difficult to meet the needs of rapid response and recovery.

Method used

By mixing the conductive filler with water ultrasonic, a uniform conductive filler dispersion is obtained, and a water-soluble polymer is added. After stirring and dissolving, a thin film is prepared on the interdigital electrode. Then the film is transferred to the non-solvent of the water-soluble polymer and left to stand to remove the solvent, thereby preparing a porous polymer humidity sensing material.

Benefits of technology

The rapid response and recovery characteristics of porous polymer humidity sensing materials are achieved, with short response time, fast recovery time, and good repeatability and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115219565B_ABST
    Figure CN115219565B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a porous polymer humidity sensing material with fast response and recovery characteristics, comprising the following steps: (1) ultrasonically mixing a conductive filler with water to obtain a uniform conductive filler dispersion; then adding a water-soluble polymer, stirring and dissolving, to obtain a polymer / conductive filler mixed dispersion; (2) using the polymer / conductive filler mixed dispersion to form a film on an interdigital electrode, then transferring the film-coated interdigital electrode to a non-solvent for the water-soluble polymer and letting it stand, taking it out and removing the solvent to obtain a product porous polymer humidity sensing material. The present invention introduces a porous structure into the polymer / conductive filler film by non-solvent-induced polymer phase separation, thereby improving its fast response and recovery characteristics. The preparation method of the present invention is simple, green and environmentally friendly, and has mild reaction conditions. The prepared porous polymer humidity sensing material has fast response and recovery characteristics, is sensitive to humidity changes, has low delay, and has good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of humidity sensitive materials, and in particular relates to a porous polymer humidity sensing material with rapid response and recovery characteristics and a preparation method thereof. Background Art

[0002] Humidity measurement is crucial in food storage, cultural relics management, drug storage, agriculture and animal husbandry, electronic product manufacturing, civil engineering and precision instrument operation. Humidity sensing materials can be used to sense changes in ambient humidity and convert them into signals that can be collected and controlled. Water-soluble polymers have strong hydrophilicity and therefore have excellent humidity sensing performance. They can be prepared into polymer-based sensing materials through specific processing techniques. However, existing polymer-based sensors generally have the disadvantage of long response and recovery times.

[0003] Humidity sensors are mainly divided into two categories: resistive humidity sensors and capacitive humidity sensors. The characteristic of resistive humidity sensors is that a film made of humidity-sensitive material is covered on the substrate. When water vapor in the air is adsorbed on the humidity-sensitive film, the resistivity and resistance value of the component change. This characteristic can be used to measure humidity; capacitive humidity sensors measure humidity by using the change of component capacitance with ambient humidity.

[0004] A Chinese patent document with publication number CN110133068A discloses a humidity sensor based on electrospun nanofiber fabric, the core components of which are composed of nanofiber fabric, metal plating and humidity sensitive material layer. The invention uses nanofiber fabric as a conductive substrate to replace the original gold interdigital electrodes, metal electrodes, etc., thereby enhancing the effect of humidity sensitive materials. However, the humidity sensor cannot return to its initial resistance value, and the response and recovery time are relatively long.

[0005] A Chinese patent document with publication number CN113189150A discloses a flexible humidity sensor based on a high molecular polymer. The flexible humidity sensor includes a flexible substrate and a flexible electrode formed on the flexible substrate by magnetron sputtering of conductive nanoparticles. The flexible electrode is located between the flexible substrates. The flexible substrate is a humidity-sensitive polymer film formed by electrostatic spinning of a high molecular polymer spinning solution doped with a humidity-sensitive material. The response time and recovery time of the flexible humidity sensor are short, but the preparation process of the flexible humidity sensor is relatively complicated.

[0006] Liu et al. reported a humidity sensor based on polyvinyl alcohol-based polymer yarn. The study spun polyvinyl alcohol and carbon nanotubes into yarn and tested the resistance change under different humidity. The sensor has good switching performance, but its response equilibrium time is about tens of minutes, and it is difficult to restore to the initial state after absorbing moisture. (Liu, Wei, Fujun, et al. A novel flexible humidity switch material based on multi-walled carbon nanotube / polyvinylalcohol composite yarn [J]. Sensors and Actuators, B. Chemical, 2016.)

[0007] Therefore, it is of great significance to develop a polymer humidity sensing material with simple preparation process, mild reaction conditions, high sensitivity, and fast response and recovery characteristics. Summary of the invention

[0008] The present invention provides a method for preparing a porous polymer humidity sensing material with fast response and recovery characteristics. The preparation method is simple, low in cost, and mild in reaction conditions. The prepared porous polymer humidity sensing material has a porous structure, is sensitive to humidity changes, has fast response and recovery characteristics, low delay, and good stability.

[0009] The specific technical solutions adopted are as follows:

[0010] A method for preparing a porous polymer humidity sensing material with rapid response and recovery characteristics comprises the following steps:

[0011] (1) ultrasonically mixing the conductive filler and water to obtain a uniform conductive filler dispersion; then adding a water-soluble polymer and stirring to dissolve the polymer / conductive filler mixed dispersion;

[0012] (2) Using the polymer / conductive filler mixed dispersion of step (1) to form a film on the interdigital electrode to obtain a coated interdigital electrode, then transferring the coated interdigital electrode to a non-solvent of a water-soluble polymer and letting it stand, taking it out and removing the solvent to prepare the porous polymer humidity sensing material with rapid response and recovery characteristics.

[0013] The present invention first prepares a polymer / conductive filler film on an interdigital electrode, and then transfers the film-coated interdigital electrode (undried) to a non-solvent of a water-soluble polymer. As water in the film is exchanged with the non-solvent, the polymer in the film undergoes phase separation, thereby generating a porous structure. The porous-based polymer material adsorbs water molecules to act as electron donors, and coordinates with the conductive filler to regulate resistance changes. The porous structure is easy to adsorb and desorb water molecules, showing faster response and recovery characteristics. In addition, the presence of the porous structure makes it less likely that water vapor will have a negative impact on its microstructure, so the present invention has strong repeatability.

[0014] Preferably, in step (1), the mass ratio of water to conductive filler is 1:0.001-0.1; too much conductive filler will cause the conductive filler to aggregate and be difficult to disperse; too little conductive filler will make it difficult to form a conductive structure in the film.

[0015] The conductive filler is nano carbon material, nano metal material, conductive polymer or conductive ceramic powder.

[0016] The nano-carbon material includes carbon nanotubes, carbon black, graphite, graphene or nano-carbon fibers; the nano-metal material includes nano-gold, nano-silver, nano-copper or nano-nickel; the conductive polymer includes polyaniline, polypyrrole or polythiophene; the conductive ceramic powder includes titanium diboride powder, tin dioxide powder or titanium carbide powder.

[0017] Preferably, the water-soluble polymer includes polyvinyl alcohol, polyethyleneimine, polyethylene oxide, polyethylene glycol, polyvinyl pyrrolidone, tapioca starch, cellulose or polyacrylamide.

[0018] In the polymer / conductive filler mixed dispersion, the mass fraction of the polymer is 1% to 20%. When the mass fraction of the polymer is too high, the solution viscosity is too large and it is difficult to perform non-solvent exchange; when the mass fraction of the polymer is too low, it is difficult to retain the pore structure after solvent exchange.

[0019] The interdigitated electrodes are alumina ceramic substrate interdigitated electrodes, PET / PI flexible interdigitated electrodes, gold modified interdigitated electrodes or silicon dioxide interdigitated electrodes.

[0020] Preferably, the film forming method includes spin coating, drop coating, blade coating or casting.

[0021] In step (3), the non-solvent for the water-soluble polymer is an alcohol solvent, an ether solvent or a ketone solvent; wherein the alcohol solvent includes ethanol, ethylene glycol, propanol, methanol, butanol, octanol, pentanol, hexanol or propylene glycol; the ether solvent includes diethyl ether, tetrahydrofuran or 1,4-dioxane; the ketone solvent includes acetone, butanone, pentanone or hexanone.

[0022] Preferably, in step (3), the standing time is 4-48 hours, and the temperature during the standing time is maintained at 4-50°C.

[0023] The present invention also provides a porous polymer humidity sensing material with rapid response and recovery characteristics obtained by the method for preparing the porous polymer humidity sensing material with rapid response and recovery characteristics. The porous polymer humidity sensing material has rapid response speed, low delay, good stability and good application potential when the humidity rises and falls.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The preparation method of the porous polymer humidity sensing material provided by the present invention is simple, green and environmentally friendly, low in cost, mild in reaction conditions, safe in process, and the raw materials are non-biotoxic.

[0026] (2) The present invention induces polymer phase separation through non-solvent, introduces a porous structure into the polymer / conductive filler film, and thereby improves the rapid response and recovery characteristics of the product porous polymer humidity sensing material, which has good application potential.

[0027] (3) The porous polymer humidity sensing material prepared by the present invention has a gradient porous structure, has fast response and recovery characteristics, is sensitive to humidity changes, has low delay, and has good stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a surface SEM image of the porous polymer humidity sensing material with fast response and recovery characteristics prepared in Example 1.

[0029] Figure 2 This is a cross-sectional SEM image of the porous polymer humidity sensing material with fast response and recovery characteristics prepared in Example 1.

[0030] Figure 3 This is a humidity response-recovery and repeated test diagram of the porous polymer humidity sensing material with fast response and recovery characteristics prepared in Example 1. DETAILED DESCRIPTION

[0031] The present invention will be further described below in conjunction with the accompanying drawings and embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0032] Example 1

[0033] 18g of deionized water and 0.02g of carbon nanotubes were mixed, and ultrasonicated for half an hour to obtain a uniform carbon nanotube dispersion; 2g of polyvinyl alcohol was added, and stirred to dissolve to obtain a uniform polyvinyl alcohol / carbon nanotube mixed dispersion;

[0034] The polyvinyl alcohol / carbon nanotube mixed dispersion was coated on the gold-modified interdigital electrode by a scraping method. The coated gold-modified interdigital electrode was transferred to a 30°C ethanol bath and allowed to stand for 24 hours. After being taken out and the solvent was dried, a porous polymer humidity sensing material with fast response and recovery characteristics was obtained.

[0035] The surface morphology of the porous polymer humidity sensing material with fast response and recovery characteristics prepared in this embodiment is as follows: Figure 1 As shown, the cross-sectional morphology is Figure 2 As shown, it can be seen that the porous polymer humidity sensing material has a pore structure, and the pore structure is gradient distributed. The polymer / conductive filler film has a better pore structure on the side in direct contact with the non-solvent. It is this gradient distributed pore structure that improves the humidity response and recovery characteristics of the porous polymer humidity sensing material.

[0036] The response characteristics of the porous polymer humidity sensing material under different humidity environments were measured. Figure 3 As shown, it can be seen that the response time of the porous polymer humidity sensing material is only about 172s when the humidity ranges from 20% to 84%, and the response time of the porous polymer humidity sensing material is about 739s when the humidity ranges from 84% to 20%. Moreover, after multiple repetitions, it still has a relatively fast response time, indicating that the porous polymer humidity sensing material has good repeatability.

[0037] Example 2

[0038] 18 g of deionized water and 0.1 g of graphene were mixed, and ultrasonicated for half an hour to obtain a uniform graphene dispersion; 0.2 g of polyvinyl pyrrolidone was then added, and stirred to dissolve to obtain a uniform polyvinyl pyrrolidone / graphene mixed dispersion;

[0039] The polyvinyl pyrrolidone / graphene mixed dispersion was coated on the gold modified interdigital electrode by spin coating, and the coated gold modified interdigital electrode was transferred to a 50°C ethylene glycol bath and allowed to stand for 8 hours. After being taken out and the solvent was dried, a porous polymer humidity sensing material with fast response and recovery characteristics was obtained.

[0040] The surface and cross-sectional morphology of the porous polymer humidity sensing material with rapid response and recovery characteristics prepared in this embodiment are similar to Figure 1 , Figure 2 It is similar to the quartz crystals, and also has a porous structure, and the pore structure is distributed in a gradient.

[0041] The polymer humidity sensing material has response characteristics under different humidity environments, and the response curve is Figure 3 Similarly, the response time from 20% to 84% humidity is only about 143s, and the recovery time is about 634s. After multiple repetitions, it still has a fast response time, showing good repeatability.

[0042] Example 3

[0043] 18g of deionized water and 0.05g of nano-gold were mixed, and ultrasonic treatment was performed for half an hour to obtain a uniform nano-gold dispersion; then 1g of polyethylene oxide was added, and the mixture was stirred and dissolved to obtain a uniform polyethylene oxide / nano-gold mixed dispersion.

[0044] The polyoxyethylene / nanogold mixed dispersion was coated on the PET / PI flexible interdigital electrode by the drop coating method. The coated PET / PI flexible interdigital electrode was transferred to a 40°C acetone bath and allowed to stand for 24 hours. After being taken out and the solvent was dried, a porous polymer humidity sensing material with fast response and recovery characteristics was obtained.

[0045] The surface and cross-sectional morphology of the porous polymer humidity sensing material with rapid response and recovery characteristics prepared in this embodiment are similar to Figure 1 , Figure 2 It is similar to the quartz crystals, and also has a porous structure, and the pore structure is distributed in a gradient.

[0046] The polymer humidity sensing material has response characteristics under different humidity environments, and the response curve is Figure 3 Similarly, the response time from 20% to 84% humidity is about 300s, and the recovery time is about 824s. After repeated tests, the response time is still fast, showing good repeatability.

[0047] Example 4

[0048] 36g of deionized water and 0.36g of nano-copper were mixed, and ultrasonic treatment was performed for half an hour to obtain a uniform nano-copper dispersion; 4g of cellulose was then added, and the mixture was stirred and dissolved to obtain a uniform cellulose / nano-copper mixed dispersion;

[0049] The cellulose / nano-copper mixed dispersion was coated on the silica interdigital electrode by a casting method, and the coated silica interdigital electrode was transferred to a 30°C tetrahydrofuran bath and allowed to stand for 28 hours. After being taken out, the solvent was dried to obtain a porous polymer humidity sensing material with fast response and recovery characteristics.

[0050] The surface and cross-sectional morphology of the porous polymer humidity sensing material with rapid response and recovery characteristics prepared in this embodiment are similar to Figure 1 , Figure 2 It is similar to the quartz crystals, and also has a porous structure, and the pore structure is distributed in a gradient.

[0051] The polymer humidity sensing material has response characteristics under different humidity environments, and the response curve is Figure 3 Similarly, the response time from 20% to 84% humidity is about 277s, and the recovery time is about 755s. After multiple repetitions, it still has a fast response time, showing good repeatability.

[0052] Example 5

[0053] 18 g of deionized water and 0.018 g of PEDOT were mixed and ultrasonicated for half an hour to obtain a uniform PEDOT dispersion; then 2 g of cassava starch was added and stirred to dissolve to obtain a uniform cassava starch / PEDOT mixed dispersion;

[0054] The cassava starch / PEDOT mixed dispersion was coated on the silica interdigital electrode by spin coating, and the coated silica interdigital electrode was transferred to a 20°C ether bath and allowed to stand for 15 hours. After being taken out, the solvent was dried to obtain a porous polymer humidity sensing material with fast response and recovery characteristics.

[0055] The surface and cross-sectional morphology of the porous polymer humidity sensing material with rapid response and recovery characteristics prepared in this embodiment are similar to Figure 1 , Figure 2 It is similar to the quartz crystals, and also has a porous structure, and the pore structure is distributed in a gradient.

[0056] The polymer humidity sensing material has response characteristics under different humidity environments, and the response curve is Figure 3 Similarly, the response time from 20% to 84% humidity is only about 265s, and the recovery time is about 898s. After multiple repetitions, it still has a fast response time, showing good repeatability.

[0057] Example 6

[0058] 18g of deionized water and 0.02g of carbon black were mixed, and ultrasonic treatment was performed for half an hour to obtain a uniform carbon black dispersion; 3g of polyvinyl alcohol was then added, and the mixture was stirred and dissolved to obtain a uniform polyvinyl alcohol / carbon black mixed dispersion;

[0059] The polyvinyl alcohol / carbon black mixed dispersion was coated on the silicon dioxide interdigital electrode by spin coating, and the coated silicon dioxide interdigital electrode was transferred to a 20°C butanol bath and allowed to stand for 48 hours. After being taken out and the solvent was dried, a porous polymer humidity sensing material with fast response and recovery characteristics was obtained.

[0060] The surface and cross-sectional morphology of the porous polymer humidity sensing material with rapid response and recovery characteristics prepared in this embodiment are similar to Figure 1 , Figure 2 It is similar to the quartz crystals, and also has a porous structure, and the pore structure is distributed in a gradient.

[0061] The polymer humidity sensing material has response characteristics under different humidity environments, and the response curve is Figure 3 Similarly, the response time from humidity 20% to 84% is only about 260s, and the recovery time is about 970s. After multiple repetitions, it still has a fast response time, showing good repeatability.

[0062] Example 7

[0063] 18g of deionized water and 0.02g of nano-nickel were mixed, and ultrasonicated for half an hour to obtain a uniform nano-nickel dispersion; 2g of polyethyleneimine was then added, and stirred to dissolve to obtain a uniform polyethyleneimine / nano-nickel mixed dispersion;

[0064] The polyethyleneimine / nano-nickel mixed dispersion was coated on the silica interdigital electrode by a scraping method. The coated silica interdigital electrode was transferred to a 20°C amyl alcohol bath and allowed to stand for 30 hours. After being taken out and the solvent was dried, a porous polymer humidity sensing material with fast response and recovery characteristics was obtained.

[0065] The surface and cross-sectional morphology of the porous polymer humidity sensing material with rapid response and recovery characteristics prepared in this embodiment are similar to Figure 1 , Figure 2 It is similar to the quartz crystals, and also has a porous structure, and the pore structure is distributed in a gradient.

[0066] The polymer humidity sensing material has response characteristics under different humidity environments, and the response curve is Figure 3 Similarly, the response time from humidity 20% to 84% is only about 254s, and the recovery time is about 1062s. After multiple repetitions, it still has a relatively fast response time, showing good repeatability.

[0067] Example 8

[0068] 18 g of deionized water and 0.018 g of polypyrrole were mixed, and ultrasonic treatment was performed for half an hour to obtain a uniform polypyrrole dispersion; then 2 g of polyoxyethylene was added, and the mixture was stirred and dissolved in a constant temperature water bath to obtain a uniform polyoxyethylene / polypyrrole mixed dispersion.

[0069] The polyoxyethylene / polypyrrole mixed dispersion was coated on the silica interdigital electrode by a scraping method. The coated silica interdigital electrode was transferred to a 20°C methanol bath and allowed to stand for 8 hours. After being taken out, the solvent was dried to obtain a porous polymer humidity sensing material with fast response and recovery characteristics.

[0070] The surface and cross-sectional morphology of the porous polymer humidity sensing material with rapid response and recovery characteristics prepared in this embodiment are similar to Figure 1 , Figure 2 It is similar to the quartz crystals, and also has a porous structure, and the pore structure is distributed in a gradient.

[0071] The polymer humidity sensing material has response characteristics under different humidity environments, and the response curve is Figure 3 Similarly, the response time from humidity 20% to 84% is only about 263s, and the recovery time is about 979s; and after multiple repetitions, it still has a relatively fast response time, showing good repeatability.

[0072] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a porous polymer humidity sensing material with fast response and recovery characteristics, characterized in that: The following steps are involved: (1) Mixing the conductive filler with water to obtain a uniform conductive filler dispersion; then adding a water-soluble polymer, stirring and dissolving, to obtain a polymer / conductive filler mixed dispersion; (2) using the polymer / conductive filler mixed dispersion of step (1) to form a film on the interdigital electrode, then transferring the film-coated interdigital electrode to a non-solvent of a water-soluble polymer and letting it stand, taking it out and removing the solvent to prepare the porous polymer humidity sensing material with rapid response and recovery characteristics; The water-soluble polymer includes polyvinyl alcohol, polyethyleneimine, polyoxyethylene, polyethylene glycol, polyvinyl pyrrolidone, tapioca starch, cellulose or polyacrylamide; The non-solvent for the water-soluble polymer is an alcohol solvent, an ether solvent or a ketone solvent.

2. The method for preparing a porous polymer humidity sensing material with rapid response and recovery characteristics according to claim 1, characterized in that: In step (1), the mass ratio of water to conductive filler is 1:0.001-0.

1.

3. The method for preparing a porous polymer humidity sensing material with fast response and recovery characteristics according to claim 1, characterized in that: The conductive filler is a nano-carbon material, a nano-metal material, a conductive polymer or a conductive ceramic powder; wherein the nano-carbon material includes carbon nanotubes, carbon black, graphite, graphene or nano-carbon fibers; the nano-metal material includes nano-gold, nano-silver, nano-copper or nano-nickel; the conductive polymer includes polyaniline, polypyrrole or polythiophene; the conductive ceramic powder includes titanium diboride powder, tin dioxide powder or titanium carbide powder.

4. The method for preparing a porous polymer humidity sensing material with rapid response and recovery characteristics according to claim 1, characterized in that: In the polymer / conductive filler mixed dispersion, the mass fraction of the polymer is 1% to 20%.

5. The method for preparing a porous polymer humidity sensing material with fast response and recovery characteristics according to claim 1, characterized in that: The interdigitated electrodes are alumina ceramic substrate interdigitated electrodes, PET / PI flexible interdigitated electrodes, gold modified interdigitated electrodes or silicon dioxide interdigitated electrodes.

6. The method for preparing a porous polymer humidity sensing material with fast response and recovery characteristics according to claim 1, characterized in that: The film-making method includes spin coating, drop coating, blade coating or casting.

7. The method for preparing a porous polymer humidity sensing material with fast response and recovery characteristics according to claim 1, characterized in that: The alcohol solvents include ethanol, ethylene glycol, propanol, methanol, butanol, octanol, pentanol, hexanol or propylene glycol; the ether solvents include diethyl ether, tetrahydrofuran or 1, 4-dioxane; the ketone solvents include acetone, butanone, pentanone or hexanone.

8. The method for preparing a porous polymer humidity sensing material with fast response and recovery characteristics according to claim 1, characterized in that: In step (2), the standing time is 4-48 h, and the temperature is maintained at 4-50°C. 9 . The porous polymer humidity sensing material with rapid response and recovery characteristics obtained by the method for preparing the porous polymer humidity sensing material with rapid response and recovery characteristics according to any one of claims 1 to 8 .

Citation Information

Patent Citations

  • Humidity sensor based on electrospinning nanofiber fabric

    CN110133068A

  • Flexible humidity sensor based on high-molecular polymer and preparation method thereof

    CN113189150A